MBO can work - Macdonald, Charles (McGraw-Hill, 1982)
Contiene: Management in a changing world. Management by contract making. Ten steps to management by contract. the larger purpose of management by contract. Detailed procedure for the functional self appraisal
Keywords: Publicidad